EVALUASI PENCATATAN ASET PADA BADAN PENGELOLAAN KEUANGAN DAN BARANG MILIK DAERAH PROVINSI SULAWESI UTARA - Primasatya, Arya Munawir; Saerang, David P.E; Mawikere, Lidia (Universitas Sam Ratulangi, 2014)
Asset recording area is a common problem in the examination of financial statements Audit Agency ( BPK ) . The resulting lack of information and errors in the presentation of accountability lead to transparency and accountability is not in accordance with the expectations of the public and other stockholders. The purpose of this study is to evaluate the suitability of the property asset recording between the management board of finance and goods belonging to the northern Sulawesi province and Permendagri No. 17 of 2007 . Evaluation is done by collecting descriptions obtained from the research through interviews and or references that relate to the problems faced. recording assets carried on the Financial Management Board and District Property North Sulawesi has followed and guided the Permendagri No. 17 Of 2007 on Guidelines for District Property Management in terms of sectoral asset management is the planning, administration, and elimination has been on the run well. Especially in terms of asset recording, beginning administration of accounting, inventory, and reporting have used SIMDA of BPKP which makes the chances of a small error in the reconciliation to achieve transparency and accountability so as to give satisfaction to the stakeholders in informed asset management area.